Analisis Yuridis Penerimaan Peserta Didik Baru (PPDB) Sistem Zonasi Region Di Indonesia: Analisis Yuridis Penerimaan Peserta Didik Baru Sistem Zonasi Region di Indonesia - Tan, Winsherly; Situmeang, Ampuan; Davina Shebiartha, Kyushu (Mendapo: Journal of Administrative Law, 2024)
Education is a vital human right that must be respected by all Indonesian people. Therefore, fair and equitable education must be provided to all levels of society. However, understanding the concept of "fairness" content of equal student citizenship is still up for dispute. Therefore, this article discusses the evaluation of New Students Accepting or Penerimaan Peserta Didik Baru (PPDB) with Regional Zoning System in Indonesia. The research method used is normative legal research in the form of analytical descriptive. Data was collected from primary and secondary sources, including primary, secondary and tertiary legal documents. This data was then analyzed qualitatively. The results of data analysis show that Minister of Education and Culture Regulation Number 44 of 2019 is unfair. This regulation prioritizes the closest location within the zoning area for middle and high school students. However, if the candidates come from the same range, then the selection is based on age, which is considered less important than the student's academic performance. Therefore, student learning achievement should be the main criterion after considering the distance from where they live. This article will discuss the need to reanalyze Law of the Minister of Education and Culture Number 44 of 2019. Factors such as student achievement must be emphasized more than their age in this process. Further efforts are needed to maintain the quality of education and increase awareness.